A halogenated solid electrolyte interface layer composite electrode material based on solid source plasma and its preparation method and application
By using the halogenated solid electrolyte interface layer formed by plasma reaction on the metal negative electrode surface of the lithium metal battery, the problems of solid-liquid interface instability and lithium dendrites in the lithium metal battery are solved, and more stable cycling performance and higher electrochemical performance are achieved.
Patent Information
- Application Number
- CN202211557530.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-06
AI Technical Summary
The instability of solid-liquid interfaces and the growth of lithium dendrites hinder their commercial application.
A halogenated solid electrolyte interface layer composite electrode material based on solid source plasma is used to form an artificial solid electrolyte interface layer on the surface of the metal negative electrode through plasma reaction, which isolates the direct contact between the metal negative electrode and the electrolyte, and provides a fast Li+ diffusion channel.
Effectively inhibit the growth of lithium dendrites, improve the stability and electrochemical performance of lithium metal, and enhance the cycle stability and safety of the battery.
Smart Images

Figure HDA0003983885870000011 
Figure HDA0003983885870000012 
Figure HDA0003983885870000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal composite negative electrode material preparation, and in particular to a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma, and a preparation method and application thereof. Background Art
[0002] At present, the development of green and clean energy to replace traditional fossil energy has reached a consensus worldwide. In order to better promote the reform of the industrial energy structure, the development of new energy storage batteries with high energy density and power density plays a very important role in this process. Lithium metal batteries have received widespread attention in recent years because they use high-capacity lithium metal (3860mAh / g) as the negative electrode. If the positive electrode is matched with conversion materials such as S, O2, etc., its energy density can reach 2600Wh / kg, which is much higher than commercial graphite lithium batteries. Although lithium metal batteries have outstanding performance in terms of capacity, energy density and power density, their cycle stability and safety performance are far inferior to commercial graphite lithium-ion batteries. Problems such as unstable solid-liquid interface, large volume expansion and irregular growth of lithium dendrites have seriously hindered the commercial application of lithium metal batteries.
[0003] In order to achieve stable cycling of lithium metal batteries and promote the commercialization of lithium metal batteries, many modification strategies have been proposed to solve a series of problems existing in batteries. These strategies can be mainly divided into the following categories: (1) Construction of a three-dimensional network current collector. As a "host-free" electrode material, the stress and strain generated by the large volume change of lithium metal during the lithium deposition / stripping process often shatters the electrode structure of the battery, causing a sharp decline in the electrochemical performance of the battery. By introducing a three-dimensional conductive host material and binding lithium in a conductive framework, the volume expansion of metallic lithium during the charge and discharge process can be effectively alleviated, maintaining the stability of the electrode structure; (2) Electrolyte modification. By using electrolyte additives to change the Li +The solvation structure of the electrolyte is obtained to obtain a solid electrolyte interface layer (SEI) mainly composed of inorganic components to inhibit the growth of lithium dendrites; (3) construct an artificial solid electrolyte interface layer. Generally speaking, the SEI film formed in situ by the electrolyte performs poorly in terms of mechanical properties and electrochemical properties. Through artificial regulation, a solid electrolyte interface layer with better performance is introduced to effectively inhibit the growth of lithium dendrites. Among the many interface layers, the interface rich in lithium halides (LiF, LiCl, LiBr, LiI) has excellent chemical stability and can effectively passivate lithium metal to prevent it from reacting with the electrolyte and causing the loss of active substances. The halogenated interface also has high interfacial energy and low lithium ion interface diffusion energy barrier, which ensures that the deposition of lithium metal is more uniform and effectively inhibits the nucleation and growth of lithium dendrites. In addition, the halogenated interface also exhibits excellent mechanical stability. The extremely high Young's modulus and shear modulus can effectively prevent the destruction of the interface during the lithium deposition process and provide support for the long-term stable cycle of the lithium metal negative electrode. As for the lithium ion conductivity of the halogenated interface, although the lithium ion bulk conductivity of the halide itself is extremely low, the introduction of the halide in the interface will greatly increase the content of grain boundaries and phase interfaces in the interface layer, which will significantly improve the lithium ion conductivity of the halogenated interface that relies on grain boundaries and phase interfaces to conduct lithium ions. Therefore, the halogenated interface shows great potential in inhibiting the growth of lithium dendrites and achieving stable lithium deposition. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma and its preparation method and application, so as to solve the problems of instability of the solid-liquid interface of the lithium metal negative electrode and lithium dendrite growth in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma is provided, comprising the following steps:
[0006] (1) In an inert gas atmosphere, a metal cathode is sealed in a plasma device and a solid source is sealed in a quartz tube;
[0007] (2) Connecting the plasma device of step (1) to a quartz tube, and then connecting the copper rings at both ends of the plasma device to a generator of a radio frequency power supply, evacuating the chamber, and after ignition, performing a plasma reaction for 30-300 seconds to obtain a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma.
[0008] The beneficial effects of the present invention are as follows: the present invention uses a solid source as a plasma excitation source to form an artificial solid electrolyte interface layer on the surface of the metal negative electrode. The interface layer can effectively isolate the direct contact between the metal negative electrode and the electrolyte, and provide a fast diffusion channel for the migration of the negative electrode metal ions. At the same time, the high interface energy of the interface layer can realize the horizontal migration of the negative electrode metal ions, thereby achieving uniform deposition and inhibiting the growth of dendrites. Therefore, the interface layer composite electrode material constructed by solid source plasma surface engineering exhibits more superior electrochemical performance and safety.
[0009] On the basis of the above technical solution, the present invention can also be improved as follows:
[0010] Furthermore, in step (1), the solid source is iodine, aluminum iodide, aluminum chloride, ammonium chloride, ammonium fluoride or zinc iodide.
[0011] Furthermore, in step (1), the solid source is iodine.
[0012] Furthermore, in step (1), the metal negative electrode is Li / Cu alloy, Li, Na, K, Zn, Mg or Al.
[0013] Furthermore, in step (1), the metal negative electrode is a Li / Cu alloy.
[0014] Furthermore, in step (1), the plasma device is composed of a quartz tube, a flange and a baffle valve.
[0015] Furthermore, in step (2), the vacuum degree is 10-100Pa.
[0016] Furthermore, in step (2), the vacuum degree is 20Pa.
[0017] Furthermore, in step (2), the radio frequency power of the plasma reaction is 50-500W.
[0018] Furthermore, in step (2), the radio frequency power of the plasma reaction is 100W.
[0019] Further, in step (2), the plasma reaction is carried out for 60 seconds.
[0020] Furthermore, in step (2), when the solid source sealed in the quartz tube is ammonium chloride, ammonium fluoride or zinc iodide, the solid source is heated at 100-300° C. after evacuation and before ignition.
[0021] Furthermore, the solid source is heated at 200°C.
[0022] The present invention also provides a composite electrode material prepared by the above-mentioned method for preparing a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma.
[0023] The present invention also provides the use of the above-mentioned halogenated solid electrolyte interface layer composite electrode material based on solid source plasma in the preparation of lithium metal battery materials.
[0024] The present invention has the following beneficial effects:
[0025] 1. The present invention uses a solid source as a plasma excitation source in a lithium metal battery. Taking I2 as an example, I2 gas is generated by sublimation. Under the excitation of a radio frequency power source, the active group of iodine is ionized and can react quickly with metallic lithium to form an LiI interface layer in situ. The interface layer is composed of inorganic polycrystalline nanoparticles with a particle size of 5nm, and is evenly distributed in the interface layer. The constructed halogenated solid electrolyte interface layer has high mechanical strength and good chemical stability, and can effectively improve the stability of lithium metal during the cycle. The halogenated interface layer can effectively isolate the direct contact between metallic lithium and the electrolyte, and provide Li + The migration of Li provides a fast diffusion channel. At the same time, the high interface energy of the halogenated interface can achieve + Horizontal migration of Li + uniform deposition.
[0026] 2. The present invention uses solid source plasma surface engineering to form a halogenated solid electrolyte interface layer on the surface of metallic lithium. By adjusting parameters such as gas flow, reaction time, and radio frequency power, halogenated interface layers of different thicknesses can be prepared in a controllable manner. In addition, in addition to being applied to lithium metal batteries, this plasma technology can also be widely used in other metal battery fields such as sodium, potassium, and zinc. It is a universal technology and therefore has great exploration value.
[0027] 3. The present invention uses solid as a plasma excitation source to construct a halogenated interface layer on the surface of metallic lithium. The halogenated interface layer formed by plasma interface engineering exhibits good electrochemical stability and low Li + The diffusion barrier and high interface energy can effectively passivate the side reactions between lithium metal and electrolyte and improve the coulombic efficiency of the battery. At the same time, the uniform chemical composition can effectively regulate the Li + Flow, induced Li + The uniform deposition of the halogenated interface layer can inhibit the growth of dendrites. Therefore, the halogenated interface layer composite electrode material constructed by solid source plasma surface engineering exhibits more superior electrochemical performance and safety, which provides the possibility for the commercial application of lithium metal batteries.
[0028] 4. The present invention is based on plasma surface engineering, and the composite negative electrode can be prepared efficiently and on a large scale, and the experimental process is simple. Therefore, the composite negative electrode has broad application prospects in the fields of mobile communications, electric vehicles, solar power generation, and aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a diagram of the plasma device in Examples 1-3;
[0030] Figure 2 This is a physical picture of the composite electrode material prepared in Example 1;
[0031] Figure 3 This is the XPS graph of the composite electrode material prepared in Example 1;
[0032] Figure 4 This is a physical picture of the composite electrode material prepared in Example 2;
[0033] Figure 5 This is the XPS graph of the composite electrode material prepared in Example 2;
[0034] Figure 6 This is a physical picture of the composite electrode material prepared in Example 3;
[0035] Figure 7 This is the XPS graph of the composite electrode material prepared in Example 3. DETAILED DESCRIPTION
[0036] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] Embodiment 1:
[0038] A halogenated solid electrolyte interface layer composite electrode material based on solid source plasma, the preparation method of which comprises the following steps: (plasma device see Figure 1 )
[0039] (1) A 50 μm thick lithium copper composite tape (Li / Cu) was punched into a 10 mm diameter disc. In an argon-filled glove box, the Li / Cu composite anode was sealed in a plasma device, and the solid source iodine was loaded in a quartz tube sealed by a custom flange;
[0040] (2) After transferring the plasma device and the quartz tube in step (1) from the glove box to the outside, they are connected with a clamp, and then copper rings are connected at both ends of the device, and the copper rings and the generator of the radio frequency power supply are connected with a wire, and vacuum is evacuated, and the radio frequency power switch is turned on. The radio frequency power is adjusted to 100 W through the control panel, and the vacuum degree in the device is controlled to 20 Pa. After ignition, a plasma reaction is carried out, and the I2 plasma reacts with the Li / Cu composite negative electrode to in-situ construct a solid electrolyte interface layer rich in lithium iodide. After the reaction lasts for 60 seconds, the radio frequency power switch is turned off to obtain a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma.
[0041] Embodiment 2:
[0042] A halogenated solid electrolyte interface layer composite electrode material based on solid source plasma, the preparation method of which comprises the following steps: (plasma device see Figure 1 )
[0043] (1) A 50 μm thick lithium copper composite tape (Li / Cu) was punched into a 10 mm diameter disc. In an argon-filled glove box, the Li / Cu composite anode was sealed in a plasma device, and the solid source NH4Cl was loaded in a quartz tube sealed by a custom flange;
[0044] (2) After transferring the plasma device and the quartz tube in step (1) from the glove box to the outside, they are connected with a clamp, and then copper rings are connected at both ends of the device, and the copper rings are connected to the generator of the radio frequency power supply with a wire, and vacuum is evacuated. The solid source NH4Cl is heated at 200°C, and the radio frequency power switch is turned on at the same time. The radio frequency power is adjusted to 50W through the control panel, and the vacuum degree in the device is controlled to 10Pa. After ignition, a plasma reaction is carried out, and the NH4Cl plasma reacts with the Li / Cu composite negative electrode to in-situ construct a lithium chloride-rich solid electrolyte interface layer. After the reaction lasts for 300s, the radio frequency power switch is turned off to obtain a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma.
[0045] Embodiment 3:
[0046] A halogenated solid electrolyte interface layer composite electrode material based on solid source plasma, the preparation method of which comprises the following steps: (plasma device see Figure 1 )
[0047] (1) A 50 μm thick lithium copper composite tape (Li / Cu) was punched into a 10 mm diameter disc. In an argon-filled glove box, the Li / Cu composite anode was sealed in a plasma device, and the solid source AlCl3 was loaded in a quartz tube sealed by a custom flange;
[0048] (2) After transferring the plasma device and the quartz tube from the glove box to the outside, they were connected with a clamp, and then copper rings were connected at both ends of the device, and the copper rings were connected to the generator of the radio frequency power supply with a wire. The device was evacuated, and the radio frequency power switch was turned on. The radio frequency power was adjusted to 500 W through the control panel, and the vacuum degree in the device was controlled to 100 Pa. After ignition, a plasma reaction was carried out, and the AlCl3 plasma reacted with the Li / Cu composite negative electrode to in-situ construct a lithium chloride-rich solid electrolyte interface layer. After the reaction lasted for 30 seconds, the radio frequency power switch was turned off to obtain a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma.
[0049] Comparative Example 1:
[0050] A 50μm thick lithium-copper composite strip (Li / Cu) is punched into a 10mm diameter disc, and the lithium-copper composite strip and iodine are placed in a closed container at the same time. The self-sublimated gaseous iodine will react with the lithium sheet to form a solid electrolyte interface layer of LiI.
[0051] Test example
[0052] 1. Physical pictures and X-ray electron spectra of the composite electrode materials prepared in Examples 1-3. The results are shown in Figure 2-7 ,Depend on Figure 2-7 It can be seen that the plasma glow colors of iodine, NH4Cl and AlCl3 are yellow, pink and white respectively; the XPS results also show the successful preparation of LiI and LiCl.
[0053] 2. Performance Testing
[0054] In an argon atmosphere glove box, the electrode materials prepared in Examples 1-3 and Comparative Example 1 were assembled into a lithium-lithium symmetrical battery, and the specific method was as follows: the electrolyte was 1 mol / L LiTFSI / DOL:DEM (1:1 volume ratio, DOL: 1,3-dioxolane; DME: ethylene glycol dimethyl ether) added with 5 wt% LiNO3, and the diaphragm was Celgard 2400; the lithium-lithium symmetrical battery was assembled in the order of positive electrode shell, composite electrode material, electrolyte, diaphragm, composite electrode material and negative electrode shell, and was pressed and sealed with a fully automatic packaging machine.
[0055] After the battery was left to stand for 24 hours, electrochemical tests were performed using a Xinwei electrochemical workstation. The electrochemical tests were all performed at 25°C, including constant current charge and discharge tests and electrochemical impedance analysis. 2 , capacity 1mAh / cm 2 Under the conditions of 0.5, 1, 2, 5, 1 mA / cm 2 Current density, 1 mAh / cm 2The battery rate performance is tested at a fixed capacity.
[0056] 1. At a current density of 1 mA / cm 2 , capacity 1mAh / cm 2 Under the conditions of , the long cycle performance of the battery is tested.
[0057] The interfacial impedances of the composite negative electrodes of Examples 1-3 before cycling were 100Ω, 120Ω, and 90Ω, respectively; after cycling for 100 h, the interfacial impedances decreased to 30Ω, 28Ω, and 25Ω, respectively.
[0058] 2. At 0.5, 1, 2, 5, 1 mA / cm 2 Current density, 1 mAh / cm 2 The battery rate performance is tested at a fixed capacity.
[0059] The cell overpotentials of the composite electrode of Example 1 were 18.3, 24.6, 42.8, and 85.4 Mv, respectively;
[0060] The cell overpotentials of the composite electrode of Example 2 were 14.3, 22.7, 40.8, and 70.4 mV, respectively;
[0061] The composite negative electrode in Example 3 exhibits the smallest overpotentials, which are 12.9, 21.3, 36.7 and 59.8 mV, respectively, indicating that it has better rate performance.
[0062] 3. At 1mA / cm 2 Current density, 1mAh / cm 2 The stable overpotentials of the lithium-lithium symmetrical batteries assembled by the three composite electrode materials of Examples 1-3 were 35.4mV, 39.7mV and 28.5mV respectively, and the batteries did not short-circuit after 2500h of cycling. However, the composite electrode material in Comparative Example 1 had a large overpotential fluctuation after 1500h of cycling, and a battery short-circuit occurred after 1800h.
[0063] It can be seen that the in-situ construction of the halogenated solid electrolyte interface layer by solid source plasma surface engineering can effectively inhibit the side reactions at the interface, making the composite electrode exhibit more stable cycle performance. The halogenated interface constructed by solid source plasma surface engineering has good mechanical strength and electrochemical stability, which can achieve Li + The uniform deposition of lithium ions can inhibit the growth of lithium dendrites. It has broad application prospects in small mobile electronic devices, electric vehicles, solar power generation, aerospace and other fields.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma, characterized in that: The following steps are involved: (1) In an inert gas atmosphere, the metal cathode is sealed in a plasma device and the solid source is sealed in a quartz tube; (2) connecting the plasma device of step (1) to a quartz tube, and then connecting the copper rings at both ends of the plasma device to the generator of a radio frequency power supply, evacuating the plasma, and after ignition, performing a plasma reaction for 30-300 seconds to obtain a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma; In step (1), the solid source is iodine, aluminum iodide, aluminum chloride, ammonium chloride or ammonium fluoride; In step (1), the metal negative electrode is Li / Cu alloy, Na or Zn; In step (2), the vacuum degree is 10-100 Pa; In step (2), the radio frequency power of the plasma reaction is 50-500W.
2. The method for preparing a halogenated solid electrolyte interface layer composite electrode material based on solid source plasma according to claim 1, characterized in that: In step (2), when the solid source sealed in the quartz tube is ammonium chloride or ammonium fluoride, the solid source is heated at 100-300°C after evacuation and before ignition.
3. The halogenated solid electrolyte interface layer composite electrode material based on solid source plasma obtained by the preparation method of the halogenated solid electrolyte interface layer composite electrode material based on solid source plasma according to claim 1 or 2.
4. Use of the halogenated solid electrolyte interface layer composite electrode material based on solid source plasma as claimed in claim 3 in the preparation of lithium metal battery materials.
Citation Information
Patent Citations
Solid electrolyte and lithium negative electrode integrated battery assembly, lithium solid-state battery and preparation method
CN115224368A